0
$\begingroup$

I am given the following triple-integral and some parameter $x > 0$

$$\int_0^{x} \int_{a-x}^{a} \int_0^{b} f(c ) \ dc \ db \ da$$

and I am asking myself whether I can rewrite this integral in the following way:

It seems, that the variable $c$ can vary between $-x$ and $x$. Thus, I am asking myself whether we can rewrite this integral as

$$\int_{-x}^{x} g(c) f(c ) \ dc$$

where $g(c)$ is a function that is to be determined.

$\endgroup$
  • $\begingroup$ Yes, by changing the order of integration so that $dc$ is on the outside. $\endgroup$ – kccu May 17 '18 at 21:34
2
$\begingroup$

Let $F(t) = \int_0^t f(u) du$ and $J$ your integral. Then $$ J = \int_0^x \int_{a-x}^a F(b) db\ da. $$ The region of integration is made of two triangles, say $T_1=co\{(0,0),(x,0),(0,-x)\}$ and $T_2=co\{(0,0),(x,0),(x,x)\}$. By exchanging the integrals and then integrating by parts you get \begin{align*} \int_{T_1} F(b) da\ db &= \int_{-x}^0 (b+x)F(b) db = \left[ F(b)\left(\frac{b^2}{2}+bx\right)\right]_{-x}^0 - \int_{-x}^0 f(b)\left(\frac{b^2}{2}+bx\right) db\\ &= \frac{x^2}{2}F(-x) - \int_{-x}^0 f(b)\left(\frac{b^2}{2} +bx\right) db\\ &= -\frac{1}{2} \int_{-x}^0 f(b) (x^2+2bx+b^2) db \end{align*} and \begin{align*} \int_{T_2} F(b) da\ db &= \int_0^x (x-b)F(b) db = \left[ F(b)\left(bx-\frac{b^2}{2}\right)\right]_0^x - \int_0^x f(b)\left(bx-\frac{b^2}{2}\right) db\\ &= \frac{x^2}{2}F(x) - \int_0^x f(b)\left(bx-\frac{b^2}{2}\right) db\\ &= \frac{1}{2} \int_0^x f(b) (x^2-2bx+b^2) db \end{align*}

This shows that the desired function $g$ is $$ g(c) = \begin{cases} -\frac{1}{2}(x+c)^2 & \text{if $c < 0$} \\ \frac{1}{2}(x-c)^2 & \text{if $c \geq 0$.} \end{cases} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.